Attitudes of Health Care Professionals on Parental Presence During Invasive Procedures and Resuscitation: A Cross-sectional Study in Eastern Nepal - Kafle, Shyam Prasad; Bhatta, Mukesh; Koirala, Namu; Koirala, Anupam (Birat Journal of Health Sciences, 2021)
Introduction: Trends are changing to allow parents and families to be with their child during invasive procedures. Because of the intense workload, there is a tendency to overlook the parents’ feelings. Attitudes of physicians and nurses are the common obstacles for this.Objective: To determine health care professionals’ attitudes toward parental presence during invasive procedures.Methodology: A cross-sectional study was conducted among the health professionals in the department of Paediatrics and Adolescent Medicine of a tertiary care center in Eastern Nepal. Ethical clearance was obtained from the Institutional Review Committee of the institute. Total sample size was 112 (83 nursing staff and 29 physicians). Attitudes of physicians and nursing staff towards parental presence during various invasive procedures were recorded in the predesigned proforma. Data was entered in MS Excel and analysed using SPSS version 21.0. Frequency, percentage, mean, standard deviation, chi-square test, independent t-test and one-way ANNOVA were used for data analysis at p